Intelligent Energy Meter for Smartcity - Shashidhara, S K; Sharath, K R; Kavyashree, M K; Basavaraj, Basavaraj; Aarif, Ibrahim B (2019 1st International Conference on Advances in Information Technology (ICAIT), 2019)
Efficient energy utilization is an important subject in the world that is filled with most of the non-renewable resources. In this paper, we are presenting Intelligent Energy meter, which is a smart Electricity measuring device that is connected to the internet via Wi-Fi that helps the direct communication with the Electricity consumers and the Electricity suppliers in terms of the number of units consumed, billing and control of the electricity flow. This electricity meter makes use of the BlynkIoT platform which provides free cloud and connectivity for the IoT devices. The proposed project is aimed at eliminating the human effort for the collection of the electricity bill from every consumer by automating the billing system through the Internet and online payment methods. This device is different from the existing systems not only in terms of the consumer authentication provided in the payment gateway and also in utilizing the industry grade online payment technology -paytm for the secured online payment.